Prediction model for energy conversion characteristics during transient processes in a mixed-flow pump. (15th May 2023) - Li, Wei; Huang, Yuxin; Ji, Leilei; Ma, Lingling; Agarwal, Ramesh K.; Awais, Muhammad
Abstract: The global energy shortage is gradually intensifying. A pump is a versatile device with significant power consumption in energy conversion equipment. Of the world's total energy generated, pumps consume about 20%. With the continuous expansion of the application field, the pump's transient working characteristics are increasingly getting important for energy saving and consumption reduction. Due to ignoring the influence of impeller rotational acceleration and fluid inertia, traditional methods have significant errors in predicting transient energy conversion characteristics, which leads to improper design and unreasonable lectotype, resulting in low pump operation efficiency. Improving the prediction accuracy of transient energy characteristics and ultimately improving the pump operation efficiency is considered to be the key solution to reducing energy consumption. Therefore, this research paper proposes a prediction model of transient energy characteristics in a mixed-flow pump. Firstly, the dynamic hydraulic torque, an important parameter of energy growth during the start-up process was calculated according to the momentum moment equation. Secondly, based on the torque energy balance equation and the relative Bernoulli equation, the transient head expression during the start-up process of the mixed-flow pump is derived, and the saddle area correction is carried out. Finally, considering the additional shaft power loss caused by the pump's backflow and clearance leakage flow, a calculation method for the instantaneous energy conversion efficiency of the mixed-flow pump is established. The accuracy of the model is compared with traditional quasi-steady-state calculation results. The results show that the predicted head of the model is in good agreement with the test head, the head estimation error is reduced from 15% to 5%, and the modified head in the saddle area is closer to the test value. In addition, this study also shows the ability of the model to simulate different start-up modes and start-up times. The models presented in this paper help guide the transient hydraulic design and prediction of transient energy characteristics of pumps. Highlights: Prediction model for transient energy characteristics of mixed-flow pump is proposed. TransIent efficiency model including turbulence loss is established. The head estimation error is reduced from 15% to 5%. The ability of simulating different start-up modes and start-up times is analyzed.